2020
DOI: 10.1016/j.mattod.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithm-guided deep learning of grain boundary diagrams: Addressing the challenge of five degrees of freedom

Abstract: Grain boundaries (GBs) often control the processing and properties of polycrystalline materials.Here, a potentially transformative research is represented by constructing GB property diagrams as functions of temperature and bulk composition, also called "complexion diagrams," as a general materials science tool on par with phase diagrams. However, a GB has five macroscopic (crystallographic) degrees of freedom (DOFs). It is essentially a "mission impossible" to construct property diagrams for GBs as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…Looking ahead, the present GNN model can be extended to describe the orientations (including three parameters for the crystal misorientation and two parameters for the orientation of the normal axis) and other features of grain boundaries 31 by assigning an additional feature vector e ij to each edge that connects node (grain) i and node (grain) j in the microstructure graph. This is similar to the application of GNN model for predicting the properties of organic molecules and inorganic crystals 23,27 where an edge vector e ij is introduced to describe the features of the chemical bond between atom i and atom j.…”
Section: Discussionmentioning
confidence: 99%
“…Looking ahead, the present GNN model can be extended to describe the orientations (including three parameters for the crystal misorientation and two parameters for the orientation of the normal axis) and other features of grain boundaries 31 by assigning an additional feature vector e ij to each edge that connects node (grain) i and node (grain) j in the microstructure graph. This is similar to the application of GNN model for predicting the properties of organic molecules and inorganic crystals 23,27 where an edge vector e ij is introduced to describe the features of the chemical bond between atom i and atom j.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that SBO can be used as a descriptor to predict and subsequently tailor GB segregation. 28 For example, if we want to promote segregation of a certain element (e.g., Cr) in HEAs, we can increase the composition of the elements with similar SBO values (e.g., Fe and Co) and/or reduce the composition of those with different SBO values (e.g., Mn and Ni). It is interesting to note that large chemicalaffinity disparity of different elements can foster segregation in HEAs.…”
Section: Generality Of the Predictions And Dft Validationmentioning
confidence: 99%
“…Notably, GB complexion (phase) diagrams, which represent GB thermodynamic states or properties as functions of thermodynamic variables such as the temperature and bulk composition (representing chemical potentials), have been developed as the GB counterparts to the bulk phase diagrams. To date, various GB diagrams have been constructed for binary and ternary systems, 19,20,26,[28][29][30] but they are rarely developed for multicomponent systems, 31 and certainly not for HEAs, owing to the increasing complexity of a large, multi-dimensional compositional space. Furthermore, the more general GBs (asymmetric GBs with mixed twist and tilt features), which are ubiquitous in polycrystalline materials and often the weak links chemically and mechanically, 28,32 are still scarcely studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOAP descriptor encodes atomic geometries with the help of a local expansion of Gaussian smeared atomic densities. The possibilities offered by these potentials are immense, allowing simulations of phenomena requiring many atoms (e.g., grain boundaries [46,47] or amorphous phases [48,49]) or accelerating the search for new crystal structures [50]. It is expected that they will impact many fields and they have already been used in the investigation of battery and potential thermoelectric materials [51,52].…”
Section: Solely Learning From Datamentioning
confidence: 99%